The Elderly-Nutrient Rich Food Score Is Associated With Biochemical Markers of Nutritional Status in European Older Adults - Kramer, Charlotte S.; Szmidt, Maria K.; Sicinska, Ewa; Brzozowska, Anna; Santoro, Aurelia; Franceschi, Claudio; de Groot, Lisette C. P. G. M.; Berendsen, Agnes A. M. (Frontiers in Nutrition, 2019)
Background: In order to prevent age-related degenerative diseases in the ageing population, their diets should be nutrient dense. For this purpose the Elderly-Nutrient rich food (E-NRF7.3) score has been developed to assess nutrient density of diets by capturing dietary reference values for older adults. To demonstrate its practical importance such score should be validated against markers of nutritional status and health. Objective: The objective of this study was to examine the association between the E-NRF7.3 score and markers of nutritional status and inflammation. Design: This study was carried out in a sample of the NU-AGE study including 242 Dutch and 210 Polish men and women, aged 65-79 years. Dietary intake was assessed by means of 7–day food records and structured questionnaires collected data on supplement use, lifestyle and socio-economic information. Baseline measurements included anthropometrics, physical and cognitive function tests, and a fasting venipuncture. E-NRF7.3 scores were calculated to estimate nutrient density of foods and the diet. Associations between the E-NRF7.3 scores and micronutrient status of vitamin D, folate, vitamin B12, homocysteine and c-reactive protein (CRP) were examined using linear regression analysis while adjusting for confounders. Results: Each one unit increase in E-NRF7.3 score was associated with a 2.2% increase in serum folate in Dutch and 1.6% increase in Polish participants in the fully adjusted models (both p <0.01). Each one unit increase in E-NRF7.3 was significantly associated with a 1.5% decrease in homocysteine levels in Dutch participants (p <0.01), whereas a 0.9% increase in vitamin B12 levels was observed in Polish participants only (p <0.01). Higher E-NRF7.3 scores were not associated with vitamin D or CRP levels. Adjustment for potential confounders did not substantially alter these results. Discussion: The E-NRF7.3 was developed to reflect dietary intake of relevant nutrients for older adults. Its association with markers of nutritional status could be confirmed for folate (both populations), vitamin B12 (Poland only), and homocysteine (the Netherlands only). There was no association with vitamin D and CRP. To further demonstrate its validity and practical implication, future studies should include a wider range of nutritional status makers, health outcomes and inflammation markers.